The Marine CoLAB: Taking a CoLABorative, Values Based Approach to Connect People to the Ocean - Chambers, Rosanna; Hart, Natalie; Ranger, Sue; Birney, Anna; Angheloiu, Corina; Loring, Jessica; Williams, Sian; Hooper, Louisa (Frontiers in Marine Science, 2019)
With growing complex and systemic challenges facing the ocean, there is an urgent need to increase the scale and effectiveness of approaches to marine conservation, including protecting and recognizing the value of all of its services. Stronger multi-sector networks of organizations are needed, sharing knowledge and working in unison to create a common narrative for the ocean and the solutions to its protection. In an innovative experiment, the Marine CoLABoration (CoLAB) brings together nine non-governmental organizations (NGOs) to explore collaboratively how to communicate more effectively. The CoLAB hypothesizes that communicating the full value of the ocean in all its rich diversity connects with people’s deeply held, personal values and leads to more impactful ocean conservation. Through horizon scanning with the wider sector, the CoLAB determines experiment themes to test this hypothesis. These are based predominantly in the United Kingdom and include #OneLess, Agents of Change and We are Ocean. The CoLAB’s work demonstrates that by effectively building and promoting an understanding of the full value of the ocean, it is possible to trigger a wider range of human values to catalyze engagement with marine conservation issues. A joined up, interdisciplinary approach to communicating why the ocean matters, engaging a wide range of actors will be crucial in effecting long term, systemic change for the ocean. The need for greater United Kingdom ocean literacy has also been highlighted across the CoLAB and its experiments and presents an opportunity for further work.